A CLASSROOM DISCOURSE ANALYSIS OF TEACHER-STUDENTS’ INTERACTION AT SMP NEGERI 7 MEDAN - Sebayang, Hizkia Junieuro; Husein, Rahmad; Harahap, Neni Afrida Sari (Jurnal Review Pendidikan dan Pengajaran, 2024)
This study aimed at analyzing the process of classroom interaction between a teacher and students at SMP Negeri 7 Medan from the perspectives of discourse analysis. It focused on how these interactions influence student engagement and learning outcomes. Using a qualitative approach, a 10-minute video recording was observed to identify key verbal and non-verbal communication patterns within the classroom. The interactions were categorized based on teacher-initiated questions, feedback, disciplinary actions, and student-initiated responses. The findings reveal that openended questions and positive reinforcement by the teacher significantly increased student participation. Conversely, disciplinary actions, though minimal, temporarily reduced engagement but improved classroom behavior. The study concludes that teacher-student communication plays a vital role in creating a productive learning environment and recommends further integration of collaborative learning strategies to enhance student involvement. This research contributes to the existing body of literature on classroom management and effective communication in Indonesian public schools.